Victims ebook - Kellerman, Jonathan (Alex Delaware, 2012)
“With his latest, [Jonathan Kellerman] not only brings his ‘A’ game but also ratchets it up a notch or three. . . . Victims will keep you up at night.”—Bookreporter   Acid-tongued Vita Berlin hadn’t a friend in the world, but whom did she cross so badly as to end up meticulously arranged in such a gruesome murder scene? One look prompts LAPD detective Milo Sturgis to summon his expert in homicidal maniacs, Alex Delaware. But even Alex is stymied when more slayings occur in the same ghastly fashion—with no apparent connection among the victims. And the only clue left behind—a blank page bearing a question mark—seems to be both a menacing taunt and a chilling cry for help from a tortured, savage soul. To end the bloody spree and prevent citywide panic, Alex navigates the secretive world of mental health treatment, from the sleek office of a Beverly Hills therapist to a shuttered mental institution where he once learned his craft. As each jagged piece of the puzzle fits into place, a portrait emerges of a sinister mind at its most unimaginable—and an evil soul at its most unspeakable. BONUS: This edition includes an excerpt from Jonathan Kellerman's Guilt.   “Expertly crafted, judiciously paced and echoing with larger social concerns.”— The Star-Ledger   “The combination of Alex Delaware [and] Detective Milo Sturgis . . . makes for the most original whodunit duo since Watson and Holmes.”—Forbes Includes an excerpt of Jonathan Kellerman’s Guilt .